MEDIA VIDEO MOTION GRAPHIC TERKAIT GAYA HIDUP SEHAT UNTUK PENCEGAHAN DIABETES MELITUS DI SMP NEGERI 12 CIMAHI - Chemil, Yohan; Rizqi, M. Aris (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: The prevalence of diabetes mellitus among adolescents under 18 years old has increased 70-fold from 2010 to 2023. Diabetes mellitus patients in the age group 5-14 years in West Java reached 12,806 people, followed by 12,409 patients in the age group 15-24 years. The prevalence of diabetes mellitus in Cimahi City for the age group ≥15 years is 675 people (2.29%). Health promotion through motion graphic video media is considered effective for educating adolescents as a measure to prevent diabetes mellitus. Objective: To develop motion graphic video media on a healthy lifestyle as a measure to prevent diabetes mellitus at SMP Negeri 12 Cimahi. Methodology: This study used the ADDIE model, including qualitative research with in-depth interviews with 5 eighth-grade adolescents selected by purposive sampling. Quantitative research was conducted with 1 content expert, 1 media expert, and 66 students selected based on proportional random sampling using feasibility test questionnaires. Results: Needs analysis revealed that students want comprehensible material, attractive media displays with bright colors, short duration, and music that supports the media's theme. Planning was structured in the form of storyboards and processed using Canva, Capcut, and Adobe Enhance. Feasibility test results showed content feasibility of 93% and media feasibility of 90%, both categorized as very feasible, and user feasibility of 79%, categorized as feasible. Conclusion: The motion graphic media on a healthy lifestyle is